Short-term impacts of COVID-19 in rural Guatemala: Call for a closer, continuous look at the food security and nutritional patterns of vulnerable families - Ceballos, Francisco; Hernandez, Manuel A.; Paz, Cynthia (International Food Policy Research Institute, 2022)
In early 2020, Guatemala reacted swiftly to the unfolding COVID-19 pandemic. It was one of the first countries in Latin America to impose strict measures to contain the spread of infection, including travel restrictions and a six-month nationwide lockdown beginning March 21 (eight days after its first reported case), comprising a temporary halt of activities in the private and public sectors, suspension of public transportation, and mobility restrictions, with a strict curfew from 6 p.m. to 5 a.m. According to the Oxford COVID-19 Government Response Tracker (OxCGRT), the country’s measures were among the top five in Latin America in terms of stringency.